Association between alcohol-impaired driving enforcement-related strategies and alcohol-impaired driving. (May 2015) - Sanem, Julia R.; Erickson, Darin J.; Rutledge, Patricia C.; Lenk, Kathleen M.; Nelson, Toben F.; Jones-Webb, Rhonda; Toomey, Traci L.
Highlights: Individual enforcement strategies were associated with less alcohol-impaired driving. A combination of strategies was associated with a larger impact on this behavior. This association remained after controlling for high-risk alcohol consumption. Enforcement agencies should prioritize using a combination of strategies. Abstract: All states in the U.S. prohibit alcohol-impaired driving but active law enforcement is necessary for effectively reducing this behavior. Sobriety checkpoints, saturation patrols, open container laws, and media campaigns related to enforcement efforts are all enforcement-related strategies for reducing alcohol-impaired driving. We conducted surveys of all state patrol agencies and a representative sample of local law enforcement agencies to assess their use of alcohol-impaired driving enforcement-related strategies and to determine the relationship between these enforcement-related strategies and self-reported alcohol-impaired driving behavior obtained from the Behavioral Risk Factor Surveillance System. We found that sobriety checkpoints, saturation patrols, and enforcement of open container laws were associated with a lower prevalence of alcohol-impaired driving but, more importantly, a combination of enforcement-related strategies was associated with a greater decrease in alcohol-impaired driving than any individual enforcement-related activity. In addition, alcohol-impaired driving enforcement-related strategies were associated with decreased alcohol-impaired driving above and beyond their association with decreased binge drinking. Results suggest law enforcement agencies should give greater priority to using a combination of strategies rather than relying on any one individual enforcement activity.